The Environmental Conservation Based on Hindu Ecotheology in the Community of Panglipuran Traditional Village, Bangli Regency, Bali Province - Mohammad Syifauddin; Kurniawan, Edi (Journal of Edugeography, 2025)
In the current era of globalization and disruption, environmental damage is becoming an increasingly complex problem. This condition requires the existence of conservation to re-articulate the relationship between humans and nature. The most important part of conservation is how to influence the mindset, character, and human behavior so that the religious and cultural approach becomes one of the strategic steps in environmental conservation efforts as implemented in the Panglipuran Traditional Village, Bangli Regency, Bali Province. This study aims to analyze the teachings of Hindu ecotheology or ecology based on Hinduism in the Panglipuran Traditional Village of Panglipuran in realizing environmental conservation. This study uses a qualitative approach with data collection methods in the form of observation, interviews, and documentation. The subjects of the research are the community and the village government of Panglipuran Traditional Village. Data analysis was performed using interactive analysis methods through the process of data reduction, data presentation, and drawing conclusions. The results showed that the Ecotheological Teachings that were believed and implemented by the community of Panglipuran Traditional Village were Tri Hita Karana teachings, which means three causes of happiness. The concept of the Tri Hita Karana teachings is a concept that regulates the relationship between humans, nature, and God which consists of the Parahyangan concept, which is the relationship between humans and God, the concept of Pawongan, the relationship between humans, and the concept of Palemahan, the relationship between humans and nature. The community of Panglipuran Traditional Village always believe and implement the Tri Hita Karana teachings in daily life so as to create a harmony between humans and nature and God. The harmony of this relationship finally creates behavior that always preserves nature and the environment as a manifestation of the beliefs they profess